An Analysis of Griceâ€™s Maxim Violation in Spider-Man: Homecoming Movie by Jon Watts - Novi Kurnia Sari; La Aso (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This thesis is intended to analyze the violation of Griceâ€™s maxim which is found in the utterances of conversations between characters in Spider-Man: Homecoming movie by Jon Watts. The research question of this study is formulated: â€œWhat are the violations of Griceâ€™s maxim found in Spider-Man: Homecoming movie?â€. The objective of this study is to find out the violations of Griceâ€™s maxim in the Spider-Man: Homecoming movie. Techniques in analyzing the data consist of describing the context of the data, presenting the data into conversations and images, explaining the data, and making the conclusion Based on the findings and discussion, the researcher concludes that all of the four types of Griceâ€™s maxim violation are found in Spider-Man: Homecoming movie. Those are the violation of quantity maxim, the violation of quality maxim, the violation of relation maxim, and the violation of manner maxim. After data reduction, it can be seen that the number of the four types of Griceâ€™s maxim violation in the movie is 20 turns. The violation of the quantity maxim is 5 turns. Violation of quality maxim is 5 turns. Violation of relation maxim is 5 turns. Violation of manner maxim is 5 turns. The dominant violation from Griceâ€™s maxim type is the violation of maxim relation. Theviolation of Griceâ€™s maxim in the movie is created in order to make the conversation seems natural as real life and not too formal for the speaker and the addressee.